Performance Evaluation and Improvement of Intersection using Sidra Intersection 8 Software: A Case Study of New Baneshwor Intersection - Auji, Sudarshan; Paudel, Jeevan; Bhatta, Santosh; Bhatt, Kailash Chandra (International Journal on Engineering Technology and Infrastructure Development, 2025)
Located at the heart of Kathmandu Valley, New Baneshwor is the busiest intersection, often faces severe congestion during peak hours as it connects four major routes: Tinkune, Maitighar, Old Baneshwor, and Sankhamul. Due to heavy traffic flow, detailed analysis of the current operational performance of the signalized intersection is mandatory and new solution should be explored. A 3-day videographic survey was carried out to count the vehicular traffic flow during peak hour from 8:30 to 11:30 and 4:00 to 7:00 in morning and evening, respectively. Additionally, pedestrian traffic was counted manually during peak hours over two days from 8:00 to 10:00 in morning and 4:00 to 6:00 in evening. Calibration and Validation were done by using ‘SIDRA Intersection 8.0’ based on average 3-day traffic volume during peak hour i.e., 9:00 to 10:00 am. The analysis depicts average delay of 338.7 seconds with LOS F, and maximum BOQ 1567.7 meters. Three alternatives including optimization of cycle length (Alternative I), combined adjustment of signal phase configuration and cycle length optimization (Alternative II), and geometric enhancement with cycle length optimization (Alternative III), were developed to improve the performance of intersection. Among them alternative III is best to optimize the performance of intersection as it improves LOS from F to D, and alleviate average delay from 338.7 to 38.8 seconds and maximum BOQ from 1567.7 to 253.9 meters.